2016
DOI: 10.1103/physrevb.94.224501
|View full text |Cite
|
Sign up to set email alerts
|

Theory of spin-selective Andreev reflection in the vortex core of a topological superconductor

Abstract: Majorana zero modes (MZMs) have been predicted to exist in the topological insulator (TI)/superconductor (SC) heterostructure. Recent spin polarized scanning tunneling microscope (STM) experiment 1 has observed spin-polarization dependence of the zero bias differential tunneling conductance at the center of vortex core, which may be attributed to the spin selective Andreev reflection, a novel property of the MZMs theoretically predicted in 1-dimensional nanowire.2 Here we consider a helical electron system des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 55 publications
6
39
0
Order By: Relevance
“…Our results agree well with Ref. [20], which shows that the helical edge states exist even in the presence of B y . In addition, the spin Hall conductance is shown in Fig.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Our results agree well with Ref. [20], which shows that the helical edge states exist even in the presence of B y . In addition, the spin Hall conductance is shown in Fig.…”
Section: Resultssupporting
confidence: 83%
“…For a QSH insulator in the presence of an out-of-plane magnetic field, the spin Chern number is shown to remain unchanged up to the magnetic field when the Landau levels cross [15,17,21]. While for an inverted InAs/GaSb quantum well in the presence of an in-plane magnetic field, the edge states and the quantized conductance are shown to be robust till a strong magnetic field of 20 T [20]. In a recent experiment, it was shown that the helical edge conduction survives up to an in-plane magnetic field of 12 T [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[42][43][44] Via an spin-polarized STM, 45,46 we can inject spin-polarized tunneling current in STS measurements and observe the zero bias conductance change caused by the SSAR from the MZM when flipping the spin of the tunneling electrons. 47,48 It is worth noting that only a small magnetic field is sufficient to excite vortices on the TI surface and hence the spin-polarized MZM in the vortex core. On the other hand, the spin polarization of other surface states and finite energy quasiparticle states is still negligibly small.…”
Section: Experimental Detection Of Mzmmentioning
confidence: 99%